2011
DOI: 10.1002/pi.3151
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure and properties of proton‐conducting sulfonated poly(ether ether ketone) (SPEEK) and zirconia–SPEEK hybrid membranes for direct alcohol fuel cells: effect of the nature of swelling solvent and incorporation of heteropolyacid

Abstract: The influence, on membrane nanostructure and properties, of water or ethanol as swelling solvent of sulfonated poly(ether ether ketone) (SPEEK) and zirconia-SPEEK hybrid membranes prepared using the sol-gel process has been investigated. Independent of the solvent, small-angle X-ray scattering measurements reveal the existence of a two-level hierarchical structure in SPEEK of greater sulfonation level, consisting of solvent-swelled spatially correlated primary SO 3 H-rich ionic clusters of around 15 Å in size,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…These ionic sites, due to their hydrophilicity, tend to phase separate from hydrophobic back bones of the polymer chains and form interconnected 3D nanochannel networks, rich of hydrophilic functional domains, which are responsible for proton conduction. [26] Kawaguti et al [27] studied these nanochannels in SPEEK. They proved that with an increase in the DS, the proton conducting nanochannels were formed more interconnected, which causes an increase in the proton conductivity.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These ionic sites, due to their hydrophilicity, tend to phase separate from hydrophobic back bones of the polymer chains and form interconnected 3D nanochannel networks, rich of hydrophilic functional domains, which are responsible for proton conduction. [26] Kawaguti et al [27] studied these nanochannels in SPEEK. They proved that with an increase in the DS, the proton conducting nanochannels were formed more interconnected, which causes an increase in the proton conductivity.…”
Section: Resultsmentioning
confidence: 98%
“…The microstructure of the hydrophilic nanochannels in hydrated sulfonated aromatic polymers can be described as being narrower, more branched and less interconnected in comparison with annealed Nafion. [27] Figure 2 shows the microstructure of SPEEK, SPPO, and SPES schematically.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 6 revealed that all the membranes exhibited a broad crystalline band at 2q ¼ 9e21 , corresponding to the ordered stacking of hydrophobic backbones [39]. Compared with SPEEK control membrane, SP-PMC-6% (Fig.…”
Section: Characterization Of the Membranesmentioning
confidence: 96%
“…Accordingly, SAXS was utilized to further probe the structure of the membrane and the results were shown in Fig. Fig.3b revealed that all the membranes exhibited a broad crystalline band at 2θ=12-25°, corresponding to the ordered stacking of hydrophobic backbone [43]. It could be found that typical scattering peaks at the q values ranging of 0.50-0.56 nm -1 were observed for all the membranes, inferring the existence of nanophase separation and ionic cluster [41].…”
Section: Microstructure Of the Membranementioning
confidence: 94%